Pelatihan Sistem Informasi Perhotelan Berbasis Web Di Hotel Deli Indah - Panjaitan, Muhammad Iqbal; Rajagukguk, Denni M; Rahmi, Elvika; Manalu, Mamed Rofendi; Sari, Ika Yusnita; Sihombing, Marjones Hardy H; Khairunisa, Khairunisa; Karo-Karo, Siddik; Maulana, Fajar; Lumbanbatu, Maristella J.; Daeli, Cosmas Samuel; Sihombing, Monang JT (CV. Devi Tara Innovations, 2024)
Advances in information technology at this time have an important role in helping human activities or work. The role of information technology is very influential in various aspects of life, both for individuals and organizations / agencies. Many organizations or agencies have utilized information technology to provide services for their business activities. However, not all business organizations have utilized the use of information systems and technology as a supporting medium for their business activities. One of them is in the field of hospitality. Hotel Deli Indah is one of the hotels located in Deli Serdang district. This hotel information is needed by the community as a place that provides several things. Such as lodging, food and drinks. However, with the website of parties who need information about the hotel, simply open the hotel website that is online and real time. To overcome these problems, we offer solutions to overcome various problems mentioned above. The solution is in the form of a Web-Based Hospitality Information System Training Application. This system was developed with the hope that it can help the hotel in terms of updating information will be easier to do where later the school information system can run faster than the current system and of course to parties who need information can directly search for hotel information by directly opening the hotel website. The objectives of PKM in general are: Can help the community in general, to disseminate information quickly, efficiently and effectively. Along with the development of Information Technology, the website no longer just offers product value, but goes to the back office system (management of office systems / agencies / schools) online and real time. The purpose of the Web-Based Hospitality Information System Training Application is to assist hotels in the process of public information services, thus providing support for better school data processing. Target to be achieved: Providing updated information media services through internet media to the wider community about Hotel Deli Indah.